The Formation and Control of Ice Crystal and Its Impact on the Quality of Frozen Aquatic Products: A Review - Mingtang Tan; Jun Mei; Jing Xie (Crystals, 2021)
Although freezing has been used to delay the deterioration of product quality and extend its shelf life, the formation of ice crystals inevitably destroys product quality. This comprehensive review describes detailed information on the effects of ice crystals on aquatic products during freezing storage. The affecting factors (including nucleation temperature, freezing point, freezing rate, and temperature fluctuation) on the size, number, distribution, and shape of ice crystals are also elaborated in detail. Meanwhile, the corresponding technologies to control ice crystals have been developed based on these affecting factors to control the formation of ice crystals by inhibiting or inducing ice crystallization. In addition, the effects of ice crystals on the water, texture, and protein of aquatic products are comprehensively discussed, and the paper tries to describe their underlying mechanisms. This review can provide an understanding of ice crystallization in the aquatic products during freezing and contribute more clues for maintaining frozen food quality.